2005
DOI: 10.1080/09585190500298420
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of dimensions of human resource management practices in Vietnam

Abstract: The purpose of this study is to extend the empirical research concerning the impact of human resource management (HRM) practices on organizational effectiveness into the context of developing and transitional economy countries. From a survey of 137 cross-sector companies, it was discovered that there are five dimensions of HRM practices currently in use in Vietnam. Variation in the application of these dimensions can be partly traced to several organizational characteristics, but most salient is the perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 36 publications
6
48
0
Order By: Relevance
“…A study using a sample from another transitional economy (Vietnam) also found a strong positive relationship between HRM and organisational effectiveness (Thang and Quang 2005). Similar to our study, market (financial) performance and organisational effectiveness were separately measured; however, the authors did not discuss the relationship between the two measures.…”
Section: Discussionsupporting
confidence: 58%
“…A study using a sample from another transitional economy (Vietnam) also found a strong positive relationship between HRM and organisational effectiveness (Thang and Quang 2005). Similar to our study, market (financial) performance and organisational effectiveness were separately measured; however, the authors did not discuss the relationship between the two measures.…”
Section: Discussionsupporting
confidence: 58%
“…This is quite consistence with earlier studies (Tung and Havlovic, 1996;Budhwar and Boyne, 2004;Thang and Quang, 2005;Wei and Lau, 2005;and Pearson et al, 2006). This means that the significant difference between them regarding age and size has made no impact at all on structure, strategy and other characteristics of HRM.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous studies in the US have found positive relations between presence of an HR department and HRM practices (Galang and Ferris, 1997). Second group includes studies which do not confirm the relationship of some organizational characteristics upon HRM (Tung and Havlovic, 1996;Poole and Jenkins, 1997;Budhwar and Boyne, 2004;Rodwell and Teo, 2004;Thang and Quang, 2005;and Pearson et al, 2006). Third group includes the studies in which researchers do realize a weak influence of organizational characteristics but considers some other influences more important than these variables (Budhwar and Sparrow 1997;Budhwar, 2000;and Andolsek and Stebe, 2005).…”
Section: Hrm and Organizational Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Bologna Process has forced universities to confront substantial changes and challenges and subsequently to rethink existing concepts of learning and teaching (European Centre for the Development of Vocational Training, 2009). What is more, effectively dealing with continuous change provides a competitive advantage (Thang & Quang, 2005), a key consideration for most contemporary higher education institutions. In the case of the context of this paper-initial teacher education (ITE) in Australia-it is also incumbent on university educators to ensure that program content and delivery prepare pre-service teachers to meet the requirements of the newly-ratified Australian Institute for Teaching and School Leadership (AITSL) National Standards for Graduate Teachers (see AITSL, 2011b), including the ability to teach effectively within the emergent K-12 National Curriculum (see Australian Curriculum and Reporting Authority, 2011).…”
Section: Introductionmentioning
confidence: 99%